2015
DOI: 10.1186/s40795-015-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of dietary intake with special emphasis on snacking pattern and nutritional status of free living adults in urban slums of Delhi: impact of nutrition transition

Abstract: BackgroundThe nutritional landscape of India is experiencing the fallout of urbanization and globalization. The changes are manifest in dietary patterns as well as health outcomes. The study aimed at assessing household dietary intake pattern with special emphasis on snacking pattern, anthropometric and lipid profiles in low socio-economic status households in an urban slum of Delhi.MethodsCommunity based cross-sectional study in 260 households of a purposively selected urban slum in North-East district of Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
1
20
2
1
Order By: Relevance
“…The nutrients were calculated using Dietsoft software (version 1.1.6) developed by the Department of Dietetics, All India Institute of Medical Sciences (AIIMS), New Delhi. The nutrients in the software are based on the values published in the "Nutritive value of Indian Foods" by ICMR, 2017 (Singh, Gupta, Ghosh, Lock, & Suparna, 2015). Questionnaire constituting of 20 and 12 questions were structured using previous studies and those referenced by Supriya (2013) and Zawila, Steib, and Hoogenboom, (2003), respectively.…”
Section: Assessment For Nk and Daily Dietary Intakementioning
confidence: 99%
“…The nutrients were calculated using Dietsoft software (version 1.1.6) developed by the Department of Dietetics, All India Institute of Medical Sciences (AIIMS), New Delhi. The nutrients in the software are based on the values published in the "Nutritive value of Indian Foods" by ICMR, 2017 (Singh, Gupta, Ghosh, Lock, & Suparna, 2015). Questionnaire constituting of 20 and 12 questions were structured using previous studies and those referenced by Supriya (2013) and Zawila, Steib, and Hoogenboom, (2003), respectively.…”
Section: Assessment For Nk and Daily Dietary Intakementioning
confidence: 99%
“…Poti et al [39] revealed that Ready-to-Eat (68.1%) and Ready-to-Heat (15.2%) products supplied the majority of energy as they contained higher saturated fat, sugar, and sodium content than unprocessed foods. Singh et al [40] revealed the association of obesity with increased intake of convenience foods. It stated that with changing dietary habits and the rise in consumption of ready-made meals, the prevalence of obesity was also increasing.…”
Section: Effect Of Convenience Foods On the Healthmentioning
confidence: 99%
“…This study used two levels of protein intake, i.e. 50 grams and 70 grams for ensuring protein security [3,17,42,50,57,58]. According to household's information, value 1 was used for protein secure households while otherwise 0 for rest.…”
Section: Mathematical Computationsmentioning
confidence: 99%
“…Where, FSIi is the food security of i th household. Household with index value of 1 were taken food secure while those with index value 0 were taken as food insecure [17,40,50,57,58]. Role of socio-economic factors in ensuring food security status among households was measured by using binary logistic regression model.…”
Section: Mathematical Computationsmentioning
confidence: 99%